Sexually transmitted disease among street dwellers in southern Ethiopia: a mixed methods study design - Negash Wakgari; Terefe Woyo; Emnet Kebede; Hirut Gemeda; Samson Gebremedhin (BMC, 2020)
Abstract Background Lack of knowledge about sexual violence, its consequences, substance use and homelessness are major problems that make street dwellers susceptible to sexually transmitted diseases. Hence, this study assessed knowledge, attitudes and treatment-seeking behaviors related to sexually transmitted diseases among street dwellers in southern Ethiopia. Methods An explanatory sequential mixed-methods study design was conducted among 842 respondents. A simple random sampling technique was used to select seven cities among fourteen major cities of the region. The sample was allocated proportionally to each selected city. In order to identify and fill in the required sample size, a snowball sampling technique was used. A pre-tested and structured interviewer-administered questionnaire was used to collect quantitative data. The collected data were entered using Epidata and exported to SPSS version 23.0 for further analysis. Unstructured questionnaires were also used to collect 21 in-depth interviews and 10 key informants' interviews. Respondents for in-depth interviews were selected purposively during quantitative data collection. Results Most street dwellers were aware of (86.7%) and had a favourable attitude towards (84.4%) prevention and management of sexually transmitted diseases. A portion of respondents experienced bad-smelling genital discharge (13.8%), genital ulcers (11.2%) and a burning sensation (14.5%) during urination, in the previous year. Among those who experienced symptoms of sexually transmitted disease, only 15.3% of them received treatment from a health care provider. Fear of questions raised by providers was one of the reasons for not seeking care according to our qualitative findings. Conclusions In this study, a significant number of street dwellers reported experiencing symptoms of a sexually transmitted disease. Despite having awareness about sexually transmitted diseases, seeking treatment from a health center was found to be low based on both quantitative and qualitative findings. We recommend that health care providers should undergo special training to address the sexual and reproductive health problems of street dwellers.